Flow characteristics and heat transfer performance of a multi-layer winding hose system: theory and experimentation. Issue 1 (March 2021) - Qiang, Haiyan; Li, Wanli; Wang, Yanran; Li, Guanyuan; Xu, Junqi
Abstract: This paper investigates the flow characteristics and heat transfer performance of a multi-layer winding hose system (MLWH) that is widely used in double-wheel trench cutters. Numerical analysis with Fluent 15.0 was performed to investigate the laminar fluid flow characteristics for the multi-layer winding hose system, especially for the study the effect of the Reynolds number and radius of curvature on the fluid flow. The radius of curvature of the multi-layer winding hydraulic hose was gradually increased in the range of 1 to 3. The Reynolds number varied between 167 and 1510. According to numerical analysis, the curvature-induced centrifugal force is found to have a significant influence on pressure drop and heat transfer. An experimental platform was presented to simulate the working conditions for the multi-layer winding hose system and collect experimental data for comparison with numerical data. The results show that the flow characteristics and heat transfer performance of the multi-layer winding hose system is strongly influenced by the Reynolds number and radius of curvature.